2012
DOI: 10.1111/j.1600-0560.2012.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry of lesional skin enhances the evaluation of cutaneous B‐cell lymphomas

Abstract: Background Cutaneous B‐cell lymphoproliferative lesions can pose diagnostic challenges. This study investigates the utlility of flow cytometry in 42 cases of suspected cutaneous B‐cell lymphoma. Methods All available cases were reviewed [World Health Organization‐European Organization for Research and Treatment of Cancer (WHO‐EORTC) classification]. Flow cytometry, immunohistochemistry and polymerase chain reaction‐immunoglobulin H (PCR‐IgH) analysis of blood and/or lesional skin were performed on primary cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 26 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…Flow cytometry is more likely to detect both CD10 and BCL2 expression and can assess light chain restriction in B cells. 14,25 Some studies have found flow cytometry to be a more-sensitive measure of clonality than immunoglobulin gene rearrangement studies by polymerase chain reaction. 14,25 Two important drawbacks in the application of flow cytometry to skin biopsies include small sample size limiting specimen adequacy 12,14 and laboratory inexperience with skin specimens; it may be technically difficult to obtain sufficient cells in small skin biopsies that are rich in stroma.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry is more likely to detect both CD10 and BCL2 expression and can assess light chain restriction in B cells. 14,25 Some studies have found flow cytometry to be a more-sensitive measure of clonality than immunoglobulin gene rearrangement studies by polymerase chain reaction. 14,25 Two important drawbacks in the application of flow cytometry to skin biopsies include small sample size limiting specimen adequacy 12,14 and laboratory inexperience with skin specimens; it may be technically difficult to obtain sufficient cells in small skin biopsies that are rich in stroma.…”
Section: Epidemiology and Clinical Featuresmentioning
confidence: 99%
“…13,18 Most cases do not spread beyond the skin (90%), although local recurrences are not uncommon (20%-30%). 2,4,[10][11][12][13]25 When it occurs, extracutaneous spread most commonly involves regional lymph nodes and the bone marrow. An important exception to the favorable prognosis in PCFCL is for PCFCL occurring on the legs.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…Sixty-three relevant articles assessing kappa and lambda IHC or ISH in the evaluation of an atypical cutaneous or mucosal lymphoid infiltrate were identified ( Table 1, Table S1). 5,[9][10][11][12][13][14][15][16][17][18] 44 papers evaluated IHC exclusively, 10,11,13,15,17,[22][23][24][25][26][27][28][29]31,32,34,35,37,40,42,45,46,[48][49][50][52][53][54][55][57][58][59][60][61][62][63][64][65][66]…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1A-F). 5,9,11,13,14,[16][17][18][22][23][24][28][29][30][31][32][33]35,38,39,41,43,44,49,50,[52][53][54]58,[60][61][62][63][64]66,68,69,72,73 16 papers exclusively examined primary cutaneous marginal zone lymphoma with kappa and lambda IHC/ISH, including lesions termed immunocytomas, amyloidomas, primary cutaneous plasmacytomas, and cutaneous follicular lymphoid hyperplasia with monotypic plasma cells. 13,14,18,24,29,30,32,43,44,[52][53]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation